MicroRNA-34a inhibits tumor invasion and metastasis in osteosarcoma partly by effecting C-IAP2 and Bcl-2 - Jie Wen; Yan-kun Zhao; Yan Liu; Jin-feng Zhao (Tumor Biology)
Osteosarcoma is a common primary malignant bone tumor that occurs mainly in children and adolescents. Recent evidence has demonstrated that miR-34a is involved in the invasion and metastasis of osteosarcoma. This study aims to explore the effect of biological behavior of miR-34a on osteosarcoma. First, we collect osteosarcoma and adjacent specimens, and the relative expression of miR-34a and C-IAP2 messenger RNA was quantitated by real-time polymerase chain reaction. Furthermore, miR-34a stimulant is synthesized and transfected onto osteosarcoma MG-63 cells. The effect of overexpression of miR-34a on osteosarcoma was detected by colony-forming assay, Annexin V-fluorescein isothiocyanate Apoptosis Detection Kit I, Transwell assay, and animal experiment in vivo. Finally, the relative levels of C-IAP2 and Bcl-2 protein were checked by western blot, and the activity of caspase-3 and caspase-9 was tested by spectrophotometry assay. In conclusion, miR-34a was downregulated in osteosarcoma cells. And the expression of C-IAP2 and Bcl-2 protein was drastically inhibited, and the activities of caspase-3 and caspase-9 were significantly increased after transfecting miR-34a onto osteosarcoma MG-63 cells. And the overexpression of miR-34a can inhibit cell invasion and metastasis, promote cell apoptosis, and arrest cells in G0/G1 period. And the animal experiment in vivo demonstrated that the overexpression of miR-34a could significantly inhibit the growth of osteosarcoma in animal skin. Taken together, we indicated that miR-34a can inhibit tumor invasion and metastasis in osteosarcoma, and its mechanism may be partly related to downregulating the expression of C-IAP2 and Bcl-2 protein directly or indirectly.